HUBUNGAN PENGETAHUAN DAN SIKAP MENGENAI INFORMASI PETA HAZARD DENGAN PRAKTIK PEKERJA DALAM MENCEGAH KECELAKAAN KERJA DI INDUSTRI MANUFAKTUR - Ihzam Ubaidillah; Ekawati Ekawati; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2021)
Hazard maps are visual representations of workplaces where there are hazards that can cause injury or illness.1 PT. Phapros Tbk is a pharmaceutical company which is one of the manufacturing sectors that produce 284 kinds of medical drugs which is classified in the ethical, generic, OTC, and Agromed product groups. One of units at PT. Phapros Tbk which has a high risk categories is the Tablets, Coated Tablets and Capsules (TTSK) because there are many potential hazard that probably can cause accident or incident. The aim of the study was to analyze relation between knowledge and attitude about hazard map information with workers practices in preventing work accident. The population in this study was all employees in the TTSK pack and process unit of PT. Phapros Tbk with a total of 50 workers. The sample used in this study was 50 workers with total sampling technique. Data was taken using a research questionnaire filled out via Google Form because researchers do not get permission to enter the company because of SARS CoV-19 pandemic so that foreigners except workers do not become agents to spreading the virus. Based on result of research by using Chi-Square Test obtained variables associated with workers practices in preventing work accident is attitude about hazard map information (p-value = 0,000). The variables that was not related to workers practices in preventing work accident is knowledge about hazard map information (p-value = 0,706). Researchers suggests to conduct a hazard mapping approach with a small group of workers or work units with some similarities in job description, so that the approach is more effective and efficient.